KINETICS OF THE INTERACTION OF POTASSIUM SUPEROXIDE WITH 18-CROWN-6 - ЕFIMOVA, IRYNA; OPEIDA, YOSYP; BESSARABOV, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The dissolution processes of KO2 in the presence of 18-crown-6 in dimethylsulfoxide (DMSO) were studied, and the properties of the complexes formed were compared with the properties of complexes with KCl, KBr, KI, and KOH (in the general case, KX). Using the electrical conductivity measurement method, the change in the electrical conductivity of the КО2 -18-crown-6 - solvent, КOH - 18-crown-6 - solvent and KBr - 18-crown-6 - solvent systems during the formation of the corresponding ions during the interaction of the crown ether with КХ was studied in solid form.Complex formation in the systems KO2-18-crown-6-solvent, KOH-18-crown-6-solvent and KBr-18-crown-6-solvent in dimethyl sulfoxide was studied. It is shown that the dependences of the specific electrical conductivity of the solution on time during the interaction of KO2, KOH and KBr c 18-crown-6 in DMSO are typical kinetic curves with asymptotes. The limiting stage is the interaction of the dissolved reagent with the surface of the solid substance. Possible kinetic mechanisms of the process were analyzed. It is shown that the change in electrical conductivity over time under these conditions is described by an exponential equation. The coefficients of this equation are determined for different systems. It is proved that the value of the parameter that characterizes the content of ions at t®¥ depends on the concentration of each of the reactants and is determined by the concentration of the one of them that is present in the mixture in the smallest amount. The resulting kinetic equations make it possible to estimate the time required to reach equilibrium. It is shown that the time to reach the asymptotic values ​​depends on the nature of the anion. The dependence of the electrical conductivity of solutions of salts and KOH in the presence of 18-crown-6 in the equilibrium state on the concentration of the components was established.It has been proved that the kinetics of the formation of the crown ether - salt complex dissociated into ions is described by an exponential equation, the parameters of which depend on the concentration of the component taken in shortage and the nature of the anion. The dependence of electrical conductivity on the composition of binary mixtures KBr - KO2, KCl - KO2, KI - KO2 was established for the first time. The resulting kinetic equations make it possible to estimate the time required to reach equilibrium. It is shown that the equilibrium solutions retain their properties for 150 hours and can be further used to study reactions involving active oxygen.
Keywords: electrical conductivity; 18-crown-6; potassium salts; dimethylsulfoxide